2010
DOI: 10.1523/jneurosci.5196-09.2010
|View full text |Cite
|
Sign up to set email alerts
|

VGLUT3 (Vesicular Glutamate Transporter Type 3) Contribution to the Regulation of Serotonergic Transmission and Anxiety

Abstract: Three different subtypes of Hϩ -dependent carriers (named VGLUT1-3) concentrate glutamate into synaptic vesicles before its exocytotic release. Neurons using other neurotransmitter than glutamate (such as cholinergic striatal interneurons and 5-HT neurons) express VGLUT3. It was recently reported that VGLUT3 increases acetylcholine vesicular filling, thereby, stimulating cholinergic transmission. This new regulatory mechanism is herein designated as vesicular-filling synergy (or vesicular synergy). In the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
198
3
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(223 citation statements)
references
References 52 publications
21
198
3
1
Order By: Relevance
“…We show that in the dorsal raphe, most of the medial serotonergic neurons are Vglut3 + and some of these also express Sert (see below), whereas the lateral neurons do not express Vglut3 but are Sert + . This is in contrast to earlier studies, in which Vglut3 and Sert expression was reported to largely colocalise (Gras et al, 2002), although a later study showed that Vglut3 and Sert are detected in distinct nerve terminals in the forebrain (Amilhon et al, 2010 neurons, Gata3 appears to be important for the full serotonergic identity of the Vglut3 + neurons (see below). Thus, distinct serotonergic precursor populations diverge soon after cell cycle exit and show differences in their requirements for terminal selector TFs (Fig.…”
Section: Generation Of Neuronal Diversity In the Dorsal Raphecontrasting
confidence: 88%
“…We show that in the dorsal raphe, most of the medial serotonergic neurons are Vglut3 + and some of these also express Sert (see below), whereas the lateral neurons do not express Vglut3 but are Sert + . This is in contrast to earlier studies, in which Vglut3 and Sert expression was reported to largely colocalise (Gras et al, 2002), although a later study showed that Vglut3 and Sert are detected in distinct nerve terminals in the forebrain (Amilhon et al, 2010 neurons, Gata3 appears to be important for the full serotonergic identity of the Vglut3 + neurons (see below). Thus, distinct serotonergic precursor populations diverge soon after cell cycle exit and show differences in their requirements for terminal selector TFs (Fig.…”
Section: Generation Of Neuronal Diversity In the Dorsal Raphecontrasting
confidence: 88%
“…We have previously observed that the vesicular coentry of glutamate through VGLUT can increase the driving force for VMAT2-mediated exchange in both mice and flies (6,54). This mechanism can increase the quantal content of DA and other cationic transmitters (6,(55)(56)(57)(58), but could also help sequester toxic VMAT2 substrates, such as 6-OHDA or 1-methyl-4-phenylpyridinium (MPP + ), away from sensitive cellular compartments or processes. Thus, increased resistance of VGLUT2-expressing DA neurons to neurotoxins is likely to explain at least some of the effects we observe following DA neuron injury with striatal 6-OHDA or systemic MPTP.…”
Section: Discussionmentioning
confidence: 99%
“…VGLUT1 is expressed by glutamatergic neurons in the hippocampus and cortex, VGLUT2 in thalamus and brainstem and VGLUT3 in scattered neurons often not associated with the release of glutamate. For example, VGLUT3 is expressed by a subset of GABAergic interneurons as well as cholinergic interneurons of the striatum and serotonergic raphe neurons (Fremeau et al 2002;Gras et al 2002Gras et al , 2008Amilhon et al 2010). In these cells, glutamate transport by VGLUT3 (and by VGLUT2 in DA neurons) both promotes vesicle filling with the other transmitter, and its release activates postsynaptic receptors, as discussed above.…”
Section: Vesicular and Plasma Membrane Transportersmentioning
confidence: 95%